The spymasters how the CIA directors shape history and the future - Whipple, Chris (Scribner, 2020)
"Only eleven men and one woman are alive today who have made the life-and-death decisions that come with running the world's most powerful and influential intelligence service. With unprecedented, deep access to nearly all these individuals plus several of their predecessors, Chris Whipple tells the story of an agency that answers to the United States president alone, but whose activities--spying, espionage, and covert action--take place on every continent. At pivotal moments, the CIA acts as a brake on rogue presidents, starting in the mid-seventies with DCI Richard Helms's refusal to conceal Richard Nixon's criminality and continuing to the present as the actions of a CIA whistleblower have ignited impeachment proceedings against Donald Trump. Since its inception in 1947, the Central Intelligence Agency has been a powerful player on the world stage, operating largely in the shadows to protect American interests. For The Spymasters, Whipple conducted extensive, exclusive interviews with nearly every living CIA director, pulling back the curtain on the world's elite spy agencies and showing how the CIA partners--or clashes--with counterparts in Britain, France, Germany, Israel, Jordan, Saudi Arabia, and Russia. Topics covered in the book include attempts by presidents to use the agency for their own ends; simmering problems in the Middle East and Asia; rogue nuclear threats; and cyberwarfare"